Nomadisme - Ferdinand, Klaus (Kuml, 1963)
Nomadism Some ecological considerations with examples from Arabia and Afghanistan 1) Pastoral nomadism 2), perhaps more than any other way of life, is bound up with one particular geographical milieu, the dry and semi-dry regions of the Old World. So striking is this connection that, if one draws on a map the contour for 250 mms. annual rainfall, one will at the same time, with minor exceptions, draw the boundary line of nomad distribution. Within this area nature provides no basis for any other mode of life than that of the wandering hunter or collector. Common to nomads and hunters is the fact that they to not, or do only superficially, interfere with the natural order among which they live. To a large degree nomads live on what nature has to offer, not directly as do hunters, but through the intermediary of their domestic animals. The flocks and herds of the nomads are in fact their most important tools in the task of winning a livelihood, and it is their domestic animals’ possibilities of thriving which set the limits for human beings’ adaptation to an often far from hospitable habitat. Water and grass, or rather grazing, are thus the fundamental factors of nomad life, but it is also an essential precondition that neither water nor grazing is in such abundance that other, more efficient types of production can thrive. Within the dryest part of the steppe a clear division has taken place, agriculturalists being found wherever water channels, wells or qanats make irrigation possible, while the rest of the area is exploited only by nomads. The situation in the socalled grass-steppes, the outer regions of the steppe proper, or in the mountains, where rainfall is more plentiful, is otherwise. Here agriculture can be practised without artificial irrigation, and the more or less latent antagonism in interests between cultivators and nomads comes into the open, with competition for use of the same land. This antagonism is most obvious when it is two widely different cultures which meet, Mongols and Chinese, or Pashtuns and Hazaras. Elsewhere this zone of greater rainfall forms a zone of transition, where all possible medial stages between nomadism and settled agriculture flourish. True nomads can be roughly divided into desert, steppe and mountain nomads, characterized -again roughly- by dependence on different animals; the desert nomads are first and foremost camel herders, the steppe nomads sheep herders, while the mountain nomads are normally somewhat less specialised, though here too sheep and goat breeding forms the basic occupation. This rule of thumb applies in particular to the Near and Middle East, the general rule being that, the more inhospitable the natural habitat, the greater need there is for mobility, and vice versa. The greatest mobility is found among desert nomads and certain steppe nomads, the least among certain mountain nomads and among half-nomads, where agriculture plays almost as important a role as the keeping of flocks and herds. Accordingly we find that camels and horses are the typical riding and pack animals on the steppes and in the deserts, while the half-nomads use predominantly oxen and donkeys. The matter of mobility leads us naturally to another prerequisite -outside contact. For the more onesided and specialised a nomad culture, the greater its need for contact with groups with other ways of life, in order to obtain essential additions to its own necessarily simple staples of life. In contrast the half-nomads have a less specialised way of life-they are pastoralists, agriculturalists, and in addition often excellent artisans. They are in fact selfsufficient, and manage very much better without outside contacts. If one visits nomads in widely separated regions one is at once struck by the basic uniformity of culture, not merely in material features of stock-keeping, of milk products, objects in daily use, dwellings and the like, but also in spiritual and social matters, attitudes to life, division of labour and structure of the communities. This uniformity is closely connected with the mobility of the nomad, and with the fact that nomad culture is the product of a long history, with considerable population movement and exchange through the millennia. It is significant that recemblances in the cultural inheritance are greater among the wideranging desert, steppe and mountain nomads, while local peculiarities are best preserved among half-nomads and more localised groups. This uniformity naturally only applies to the basic features of nomad life. Each individual culture has its own distinctive coloration, more obviously in its material equipment. This distinctive coloration is largely dependent on the outside contacts of each individual nomad culture, for nomads are not "provincial"-they have wide contacts with other population groups and a considerable acquaintance with other cultures and ways of life than their own. The Asiatic and North African nomads live -and have lived for millennia- in the midst or on the very edge of the regions of ancient Asiatic civilization, and from these civilized neighbours the nomads have assimilated -and still to an increasing degree assimilate- whatever new features can be fitted into their way of life -and indeed preferably a little more than can comfortably be absorbed, with a view to prestige. Of particular significance is the fact that nomads do not differ in religion from the surrounding culture groups, and all today belong to one or another of the main religions of the world. It is therefore essential for an understanding of pastoral nomadism to remember constantly that the economic basis rests not merely upon a specialized adjustment to the natural habitat but also upon an adjustment to the surrounding cultural milieu, an adjustment which shows itself in cooperation with the neighbouring agriculturalists, and in varying degrees of contact with artisans and merchants. The specialization of the nomads is in fact only possible on a basis of this cooperation with groups with other ways of living. To some degree the connection between nomads and settled communities is symbiotic, and each group is dependent on the other. But the dependence is not equal; the settled communities can, without great hardship, dispense with contact with the nomads, whereas the nomads would not be able to maintain their way of life at all without contact with farmers and artisans. They are therefore in a position of compulsory dependence upon their settled environment around them, forced upon them by the shape their culture and way of life has assumed. It is from this angle that certain examples of true nomadism are described, with particular reference to the relationship between the nomads and the settled population, and how this is in the last resort governed by political factors. South Arabia, Qatar The traditional life of the Murra tribe is based on the camel, their universal provider, which is used as riding and pack animal, as source of milk and meat, as well as of wool for weaving and dung for fuel -the camel is the essential precondition for life in the desert. Despite the fact that the Murra are more skilled at handicrafts than, for example, the Afghan nomads, and live an extremely spartan life they still have need for outside contacts, through which they obtain a large part of the necessities of daily life, dates and flour, coffee and sugar, cotton garments and all types of metal utensils. Formerly they obtained these things by sale of their own products, by protection of caravans and -not the least important- simply by taking them. We know from Palgrave how in former days the Murra and other tribes from time to time plundered the villagers of Qatar 6). But that is a thing of the past. The Murra are now pacified and have secured their position by submission to the sheikh of Qatar, who is in a strong position on account of oil royalties. They now receive from him the supplies which they formerly had to take for themselves. But the benefits are reciprocal. The ruler of Qatar has need of loyal subjects; they form, as it were, a standing army for him. And the beduin receive security. (Examples are given of how this situation works in practice. A certain competitiveness among the sheikhs of the Gulf to win the loyalty of the beduin is noted). While the traditional life of the beduin thus continues, with subsidies, in South Qatar, in North Quatar the beduin (Na’im) are undergoing a revolutionary change of life; all men of working age have found employment in the oil company, and only come home to the camp at the weekends (1959). The course of events in Qatar is very different from that in other Arab states. Here nomadism and tribal structure is, practically speaking, subsidised and preserved; but the fact of the matter is that the government of the country is closely bound up with, even to some extent based upon, tribal loyalties. In Qatar a traditional tribal-feudalist government is -thanks to an abundance of money- in process of development into a modem welfare-state. East Afghanistan The differences from South Arabia are considerable. The climate is not so hot or so dry, and the enormous differences in altitude provide a basic rythm of seasonal migration between the lowlands and the mountains. The life of the nomads is not so subject to natural catastrophe; by reason of the considerable winter snowfall in the mountains water is no real problem and there is seldom any risk of overgrazing. There is yet another characteristic difference: the nomads are throughout the year in constant contact with well-established settled communities. This provides the background for a high degree of specialisation on the part of the nomads, reflected in their dependence on the non-nomads. Flour of maize and wheat, mulberries and rice are necessities, and they acquire these from outside, together with implements of wood and metal, cotten garments and ornaments, even tent material and all forms of woven sacks for transport, none of which are made by the nomads themselves. In return they can offer principally dairy produce and meat of sheep and goats. They are true nomads, owning only their flocks of sheep and goats, their camels and what they carry with them. In addition they have traditional grazing rights over certain parts of their winter and summer range, areas which they call their own and over which their ownership, in the case of the summer range, has been ratified by the government; and more or less timehonoured rights to their migration routes, though here they have no monopoly of rights. Use of the various migration routes is governed largely by the friendships and enmities at any one time existing between the tribes. The reciprocal dependence upon each other of nomad and farmer shows itself in various details: the nomads may during migration freely take mulberries for their own use; they often weed the farmers’ fields and use the weeds as fodder; on the spring and particularly the autumn camp sites the nomads camp and graze the harvested fields of the farmers, and "pay in cash" by manuring. If, however, we look deeper into the contact between nomad and farmer we come to the purely economic transactions and from there by imperceptible degrees to the political plane; for despite the symbiosis between them -or perhaps because of it- there exist clashes of interests which in the final resort are settled by power politics, force and the threat of force. This can be illustrated by two examples from East Afghanistan, the first a case where practical equilibrium has been reached between nomad and settled, though with a slight dominance on the part of the settled, the other a case where the nomads dominate and are the expanding party. (A detailed presentation can be found in the Proceedings of the VII International Congress of the Ethnological and Anthropological Sciences, Moscow, August 1964 (forthcoming)). 1. This concerns a smallish group, 150-200 tents, mainly of the Tarrakhel, with a limited range of migration (about sixty miles) from a winter area at Laghman in Ningarhar Province (in close association with villagers, to whom they supply wood from the mountains in exchange for farm produce) to a summer specialised for life near the capital Kabul, where they sell cheese (pa. potse, p. panir-i-pokhta) in the bazaars for cash. The are specialised to such a degree that it is justified to call them "cheese-nomads". In economic relations there is no obvious tendency for the one part of the nomad-settled symbiosis to dominate over the other. A dominance will in fact, in every individual case, be discernible, but only on that individual level, as the largest economic unit is the single tent. For the nomads have no central authority, but are divided into a number of segments, each with a leader approved by the government and not necessarily having any influence outside his own group. In practice, if economic or personal conflicts of a certain degree of seriousness arise, they are always settled outside the nomads’ own tribal system, by the dominant settled Pashtun khans of the summer and winter areas. And if these cannot settle the dispute the Afghan authorities step in. For this tribal group is in fact completely integrated into the Afghan administrative system: births must be registered, all adult men possess identity cards (which involves the tribe supplying the government with soldiers), taxes are paid in accordance with the number of animals owned, and so on. There is thus no question of the natural interplay of power -the government is more or less involved in everything. Although the nomads are in general not pleased with this state of affairs it can sometimes work to their advantage. It did so when the farmers in the summer area tried to deny the traditional grazing rights of the nomads, pointing to the damage done to their fields. The government upheld the rights of the nomads, and in this way helped to maintain the status quo. It should be noted, though, that this group of nomads, being more or less confined in its summer and winter areas, is to an increasing degree open to pressure from the settled peoples around them. The nomads complain, too, that things are no longer as they were in the old days when they were capable of making themselves respected by the farmers with their sticks. This, though, is undoubtedly a somewhat idealised picture of the old days, as the group has certainly lived for several generations in the way outlined here. 2. The next group comprises the wide-ranging nomads (Ahmadzai, Mohmand), who migrate from lower East Afghanistan and from Pakistan to Hazarajat, a distance of up to 300 miles. These peoples are and were primarily sheep raisers. Their summer area is of recent acquisition; in the 1890’s the nomads assisted the government to subdue the Hazara, and as a reward they were allotted grazing areas in Hazarajat. A division took place, the Hazara farmers living on and farming the lower land (though up to 3300 meters above sea level), while the nomads live even higher. As the nomads and the Hazara have radically different cultures -in particular belonging to different religious sects, the nomads being Sunni and the farmers Shi’a- there is a particularly sharp tone to the relationship between them. The economy of the Hazara is broadly based. They practise mixed farming, and there is therefore no basis for the usual barter between nomads and farmers of dairy produce against agricultural products. Thus if the nomads are not to take by force what they need of the farmers’ produce they are forced to buy for cash. Now trade is no foreign idea to the Eeast Afghan nomad, and caravan transport has always been a subsidiary occupation. In Hazarajat there was a virgin market; and in this area we therefore see trade for the sake of trade increase enormously, in the case of some tribes to a degree such that their original occupation of sheep breeding has receded more and more into the background, and one can now truly call them trade-nomads. This gradual commercialising of pure nomads is not peculiar to Hazarajat. A similar development has undoubtedly taken place in other regions in East Afghanistan more os less continuously throughout history. The trade of the nomads takes place on three levels: 1) neighbourhood trade, where the nomads trade with the settled Hazara in the neighbourhood of their summer area, 2) long-distance trade based on trading caravans, and 3) trade in the large nomad bazaars which are held each summer in the heart of Afghanistan. I shall confine myself here to describing the neighbourhood trade 8). Briefly, the Hazara supply wheat, clarified butter, and woven articles, and receive from the nomads bazaar goods, primarily cheap Pakistani cotton cloth, unrefined sugar, tea, and a variety of other goods; and -very important- credit on goods delivered, as well as advance payment for future deliveries. The point is that the Hazara are more or less constantly short of cash. The nomads usually buy clarified butter (ghee) and wheat for their own consumption, but to an even greater extent for taking eastward for re-sale, thus giving nomads with liquid means an extra advantage; for in the ghee and wheat trade there is generally a gross profit of at least 100 % per year. Let me exemplify the method. Nomads buy wheat for delivery the next year, and pay for instance about 10 Afghani per ser (which is 7 kilos). Next year the Hazara is unable to supply the wheat. He is then obliged to buy back the amount of wheat he owes the nomad, but now at the current price of about 25-30 Afghani per ser. If now the peasant is unable to pay this sum in cash it is converted once more to wheat, again on the advance payment basis of 10 Afghani per ser, which means that next year he has to deliver 2½-3 ser of wheat for every one ser contracted for this year. If unable to pay next year the calculation again continues as described, and the peasant sinks deeped and deeper into debt. The articles which the Hazara buy from the nomads (whether clothes, tea or sugar) are seldom, if ever, paid for in cash. Instead, the debt is written down and falls due for payment the following year -and is very often reckoned in wheat calculated on the basis here outlined- a most profitable system for the nomads. The backbone of this nomad trade, especially in earlier days, was cheap cotton clothing, and the nomads preferred to give this as payment for all provisions, as it was the most remunerative. For obvious reasons the nomads are generous with credit. As they told me: "If a man wants to borrow 100 Afghani, we always give him 200". This system is a vicious circle for the Hazara; as settlement of unredeemed debt the nomads take over sheep, cows, and in the last resort land. But the nomads do not on that account become good peasants; on the contrary they let out the land to some Hazara to till as a share-paid tenant. And by this arrangement the nomad has still further secured his livelihood. The economic relations between nomads and settled farmers in this area have as one of their most important motive forces the fact that neither party desires cash settlement, owing, respectively, to lack of money and to regard for profit. And the result is that the nomads are, slowly but surely, in process of establishing themselves as a land-owning upper class, which each year returns to fetch its yield. The relations between nomads and the settled Hazara have more aspects than I have been able to deal with here; but the tendency is obvious. The nomads are economically dominant and expanding. And this accords moreover with political dominance -the nomads are the stronger. The government has acquiesced in this situation, though there are now indications that it will attempt to redress the balance. The Hazara themselves have been unable to do anything; they have been caught in a vicious circle, and submission, or flight to the cities, are -to put it very roughly- the only ends in sight for them. Let me amplify the statement about the strength of the nomads. They are well armed and numerous -several thousand tents in the whole of Hazarajat. And though the government year by year limits the independence of the nomads those here described are still not issued with identity cards and consequently do not supply the government with troops. These factors all contribute to the dominance of the nomads. In the two Afghan cases here presented there are two basic constants: a fairly uniform habitat, and a fairly uniform nomad culture. Such differences as exist have largely arisen in the course of adjustment to, and under influence from, the variant cultural background of the settled peoples around them. In both cases, too, as well as in the case of the Murra, it can be seen how the existing political structure decisively influences relations between settled communities and nomads, where one part will often be the dominant. But the relationship between farmers and nomads is not only a question of one group’s dominance over the other. In a wider context it is the balancing of two livelihoods in relation to each other; and not least in the exploitation of the natural habitat. We know from history and it is true both of the Near East and of Central Asia- that political instability, war, and unstable conditions in general seem to encourage nomadism, while ordered, peaceful conditions under a strong settled power limit nomadism and encourage agriculture. It is primarily in the zone of the grass-steppe that these fluctuations occur; for here competition is for the same land, just as it can be seen in Hazarajat, where many nomad grazing grounds have previously been under the plough. Where the opposing cultures are not of widely different character the fluctuations occur, as it were, internally. We know from the Arab world how times of troubles have forced farmers into semi-nomadism, and semi-nomads into true nomadism, and how the reverse process can take place under peaceful conditions. It is the peaceful process which we know best, though not from detailed study; and it is that, too, which at the moment is causing the widespread sedentarisation which is found, under many different forms, throughout the whole nomad region. The opposite process -of nomadisation- has only been seen in glimpses (during the war, for example, there was a renaissance of nomadism in Iran), and the factor which here operate are, in my opinion, 1) that in times of troubles people seek protection in the greater mobility of nomad life, and 2) that the latent military character of nomadism has then free rein. (It is typical of true nomadism at all levels of social structure that it can be speedily adapted to campaigning). In order fully to understand the processes at work in the relationship between nomads and settled peoples, good detailed studies are necessary, and in particular trustworthy demographic material. So far as I know, this is only very sparsely available. Barth, for example, shows in the case of the Basseri in South Iran that the nomad population increases at a faster rate than the settled populace. But as the nomad population is fairly constant, a movement away from nomadism must be taking place. This occurs at two levels, partly by the rich becoming settled landowners, partly by the poor moving to the villages and towns as a proletariat. Although I can refer to no statistical material, it is clear from my results that something similar is happening in Afghanistan. Let us first look at the rich, the owners of capital. The trading activities which I have described are in reality a stage on the way to settlement, a fact which is the result of the limited possibilities for economic expansion within pure pastoralism. Wealth among nomads is measured primarily in number of livestock. Now, the natural environment in Afghanistan -the size of the grazing area- sets a direct limit to the number of livestock a man can own -and the more he has, the less yield they give per head. Capital invested in livestock alone is vulnerable capital: drought, sickness, and in former days war and raiding can very speedily ruin a nomad totally. This is the reason why the rich nomads insure themselves by buying land, and in Afghanistan this happens, as we have seen, frequently through the agency of trade. This does not automatically involve the nomad settling down; they prefer to continue their wandering life, moving from estate to estate, and taking from each the agricultural produce so necessary to their way of life. Nevertheless, in the course of time the most businesslike and the luckiest settle down. They first become landlords, and then, after a couple of generations of division and subdivision of land, their descendants may become actual and competent farmers. But the process goes via the landlord stage. In the case of the poor, the ruined nomads, the process is not so uniform. Primarily they seek employment. They may become shepherds, but very often they look for work with the farmers (though not with the Hazara); often they become itinerant harvesters, and from this stage they may be able to work their way up to being pure nomads again. Otherwise they end as landless settlers. These two processes are not of completely recent origin. Many East Afghan villages are inhabited by descendants of former nomads. But the impetus towards acquiring land is now stronger than ever before, a fact which once more has a political basis. It is now the writ of the Afghan government and not of the nomads themselves which runs throughout the country. In this article I have aimed to throw light on nomadism by looking to the ecological factors as they have developed through adjustment to both the natural and the cultural milieu which surrounds the nomad, and to show how the nomad is culturally and socially "equipped" to exploit definite resources in this milieu, but also how that same "equipment" sets quite wide limits to adjustment to changes in the milieu. Nomadism is, one may say, extraordinarily sensitive to milieu, so sensitive, in fact, that the bounds of this way of living are continually being burst and a change in the whole way of life resulting. H. P. Steensby’s characterisation of nomadism as a blind alley 12) in historical development is very apt. For no lines go forward from nomadism to more "developed" forms of society. Nomadism is a "branch-line" -but a branch- line which even in our day has full justification. For none other than the wandering nomad is capable of converting the sparse vegetation of the steppe to animal protein, for which there is such a crying need with the continually increasing settled population of the world’s many poor countries. Rather than trying to eliminate the nomad way of life, as is being attempted in many of the new national states, it would be more fruitful to assist and modernise nomadism, in order that it might be even more productive. Klaus Ferdinand